Pembelajaran Bahasa Inggris IslamiMelalui Hand Lettering - Muhamad Dini Handoko (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
One means of learning English that uses Islamic methods is Hand Lettering. Thus it is hoped that through this method the teachers and the participants can master the English language and also get its Islamic values in the process. Hand lettering is the art of writing letters that generally speak English. But all these things are directly related to letters or writing. It is hoped that Hand Lettering will be able to bridge the learning of Islamic English between teachers and students, as well as the environment. This type of research is Classroom Action Research (PTK) which aims to improve the activities and learning outcomes of learners through Hand Lettering. Objects in this classroom action research are semester V learners totaling 30 students.